Gastropod Community Structure as a Bioindicator of Water Quality n The Seagrass Ecosystem at Samuh Beach, Bali - Pratama, Made Dendy; I Putu Gede Eka Handrayana Putra; I Kade Alfian Kusuma Wirayuda (Jurnal Biologi Tropis, 2025)
Coastal ecosystems, such as the seagrass meadows at Samuh Beach, Bali, are vulnerable to anthropogenic pressures from high-intensity tourism. This degradation necessitates effective monitoring tools, and gastropod communities are potential bioindicators due to their sensitivity to environmental change. The objective of this study was to evaluate the gastropod community structure as a bioindicator of water quality within this ecosystem. The study was conducted from November to December 2024 at two stations representing different levels of human activity, using line transects and quadrat sampling. A total of 10 gastropod species were recorded. The community structure was characterized by low species diversity (H' = 1.25), moderate evenness (E = 0.52), and low dominance (C = 0.35). In contrast, all measured water quality parameters were found to be within optimal ranges for marine biota. The dissonance between the low biodiversity and favorable water chemistry suggests that the gastropod community is responding to unmeasured stressors, likely physical disturbances or specific pollutants associated with tourism. This study validates the efficacy of using gastropod assemblages as sensitive bioindicators of ecosystem health, capable of detecting impacts that standard water quality tests may miss. Continuous monitoring is recommended to safeguard the area.